A New Type-2 Soft Set: Type-2 Soft Graphs and Their Applications - Khizar Hayat; Muhammad Irfan Ali; Bing-Yuan Cao; Xiao-Peng Yang (Advances in Fuzzy Systems)
The correspondence between a vertex and its neighbors has an essential role in the structure of a graph. Type-2 soft sets are also based on the correspondence of primary parameters and underlying parameters. In this study, we present an application of type-2 soft sets in graph theory. We introduce vertex-neighbors based type-2 soft sets over X (set of all vertices of a graph) and E (set of all edges of a graph). Moreover, we introduce some type-2 soft operations in graphs by presenting several examples to demonstrate these new concepts. Finally, we describe an application of type-2 soft graphs in communication networks and present procedure as an algorithm.